2023
DOI: 10.1002/cncr.34633
|View full text |Cite
|
Sign up to set email alerts
|

Emotional, behavioral, and physical health consequences of loneliness in young adult survivors of childhood cancer: Results from the Childhood Cancer Survivor Study

Abstract: Background Young adults in the general population are at risk of experiencing loneliness, which has been associated with physical and mental health morbidities. The prevalence and consequences of loneliness in young adult survivors of childhood cancer remain unknown. Methods A total of 9664 young adult survivors of childhood cancer (median age at diagnosis 10.5 years [interquartile range (IQR), 5–15], 27.1 years at baseline [IQR, 23–32]) and 2221 siblings enrolled in the Childhood Cancer Survivor Study complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…However, analyses revealed an indirect association between reduced social attention and more social impairments through angry FER. These findings are significant given the risks posed by poor social adjustment and isolation to the wellbeing of SPBT, including increased psychological distress, 37 suicidal ideation, risky health behaviors, and new‐onset chronic conditions 7 . Moreover, social information processing—and more specifically, underlying social affective functions—influences social behavior and social adjustment 14,15 .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…However, analyses revealed an indirect association between reduced social attention and more social impairments through angry FER. These findings are significant given the risks posed by poor social adjustment and isolation to the wellbeing of SPBT, including increased psychological distress, 37 suicidal ideation, risky health behaviors, and new‐onset chronic conditions 7 . Moreover, social information processing—and more specifically, underlying social affective functions—influences social behavior and social adjustment 14,15 .…”
Section: Discussionmentioning
confidence: 96%
“…These findings are significant given the risks posed by poor social adjustment and isolation to the wellbeing of SPBT, including increased psychological distress, 37 suicidal ideation, risky health behaviors, and new-onset chronic conditions. 7 Moreover, social information processing-and more specifically, underlying social affective functions-influences social behavior and social adjustment. 14,15 Previous research with SPBT has focused on social attention and face processing as predictors of social impairments, 17,[20][21][22] less and worse peer interactions, 18 and fewer friendships.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the growing interest in investigating social isolation in recent years, researchers have confirmed that social isolation, or loneliness, has numerous adverse effects on the health status of cancer patients [19,20]. Studies have found that social isolation or loneliness was a risk factor for the following physical and mental statuses: malnutrition, new-onset chronic conditions, risky health behaviors, anxiety, constructive coping, depression, illness acceptance, and suicidal ideation [21][22][23][24]. Additionally, there was evidence that social isolation and loneliness were even related to all-cause and cancer mortality [25].…”
Section: The Adverse Effects Of Social Isolation or Lonelinessmentioning
confidence: 99%
“…In addition to concerns and management of their ongoing or potential health issues, adolescent cancer survivors face tasks common to of their peers, such as navigating the social landscape of school, building a career path towards independent adulthood, and finding their place as contributing members of society [5][6][7][8]. Prior studies have indicated that adolescent cancer survivors who experience difficulties returning to normal life may be at increased risk of unemployment and social isolation [8][9][10][11]. A study conducted in ROK on 145 adolescent cancer survivors aged 13-18 years revealed that 49.7% reported experiencing at least one type of peer exclusion and victimization in school [12].…”
Section: Introductionmentioning
confidence: 99%